Pengaruh Konsentrasi NAA dan BAP terhadap Induksi Kalus Gambir (Uncaria gambir Roxb.) - Rita Elfianis; Rohmat Firdaus; Oksana; Nida Wafiqah Nabila M. ` Solin (Program Studi Agroteknologi INSTIPER, 2026)
Gambier is generally propagated both generatively and vegetatively. However, these methods require a long time and often result in non uniform quality. Tissue culture is an alternative technique that can improve gambier quality within a relatively shorter period through callus induction. This Study aimed to determine the best concentrations of NAA, BAP, and their combination for inducing callus. This research was conducted at the Reproduction and Breeding Laboratory of Sultan Syarif Kasim Riau State Islamic University. This study employed an experimental method using a factorial Randomized Block Design (RBD). The first factor was the concentration of NAA (0 mg/L, 0.25 mg/L, 0.5 mg/L, 0.75 mg/L, 1 mg/L), while the second factor was the concentration of BAP (0 mg/L, 0.75 mg/L, 1.5 mg/L, 2.25 mg/L). In total, 20 treatment combinations were arranged in five replications. The observed parameters includes time to callus initiation, percentage of callus formation, callus texture, and callus color. The results showed that NAA at 0.5 mg/L was the best concentration for gambier callus induction, while BAP at 1.5 mg/L was also optimal for the purpose. The combination of 0.5 mg/L NAA and 1.5 mg/L BAP was the best treatment, accelerating callus initiation to 15.1 days after planting (DAP), with 50% yellowish-white callus and 60% friable texture.